Development of a teledermatopathology consultation system using virtual slides - Nakayama Ikunori; Matsumura Tsubasa; Kamataki Akihisa; Uzuki Miwa; Saito Kenji; Hobbs James; Akasaka Toshihide; Sawai Takashi (BMC, 2012)
Abstract Background An online consultation system using virtual slides (whole slide images; WSI) has been developed for pathological diagnosis, and could help compensate for the shortage of pathologists, especially in the field of dermatopathology and in other fields dealing with difficult cases. This study focused on the performance and future potential of the system. Method In our system, histological specimens on slide glasses are digitalized by a virtual slide instrument, converted into web data, and up-loaded to an open server. Using our own purpose-built online system, we then input patient details such as age, gender, affected region, clinical data, past history and other related items. We next select up to ten consultants. Finally we send an e-mail to all consultants simultaneously through a single command. The consultant receives an e-mail containing an ID and password which is used to access the open server and inspect the images and other data associated with the case. The consultant makes a diagnosis, which is sent to us along with comments. Because this was a pilot study, we also conducted several questionnaires with consultants concerning the quality of images, operability, usability, and other issues. Results We solicited consultations for 36 cases, including cases of tumor, and involving one to eight consultants in the field of dermatopathology. No problems were noted concerning the images or the functioning of the system on the sender or receiver sides. The quickest diagnosis was received only 18 minutes after sending our data. This is much faster than in conventional consultation using glass slides. There were no major problems relating to the diagnosis, although there were some minor differences of opinion between consultants. The results of questionnaires answered by many consultants confirmed the usability of this system for pathological consultation. (16 out of 23 consultants.) Conclusion We have developed a novel teledermatopathological consultation system using virtual slides, and investigated the usefulness of the system. The results demonstrate that our system can be a useful tool for international medical work, and we anticipate its wider application in the future. Virtual slides The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1902376044831574